Perlindungan Hukum Bagi Konsumen Dalam Kasus Gagal Bayar Klaim Asuransi Di Indonesia - Kushertin, Juli; Abadi, Suwarno; Daim, Nuryanto A. (Law and Humanity, 2024)
Good corporate governance or better known as Good Corporate Governance is a value system that is a benchmark for a company's ability to carry out operational activities and business processes in a healthy manner. The Financial Services Authority (OJK), which was formed in accordance with Republic of Indonesia Law Number 21 of 2011, is not running effectively and is considered to have been negligent in its supervision process, resulting in actions involving deviant practices such as corruption and money laundering in the case of PT Asuransi Jiwasraya consumer failure to pay. Law enforcement in order to guarantee that the public gets their rights, consumers who fail to pay PT Asuransi Jiwasraya (Persero) have found a solution through restructuring. So that urgent changes can be implemented ably by the state, financial sector reform Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector exists as legal protection. Legal protection is carried out to restore trust. Legal protection is the state's effort to compile the achievements of the Indonesian Long Term Development Plan (RPJPN) 2025-2045 as part of legal development. The aim of the research is to determine law enforcement and legal protection from criminal acts of corruption in the financial sector which operates in the insurance sector, case study PT Asuransi Jiwasraya which has a progressive legal correlation of asset confiscation. The type of research, problem approach, theory used is normative legal research with a statutory approach with a conceptual approach. The theory used to analyze is the basic theory of Lex Specialis Derogat Legi Generalis. The research results show that the application of law and corporate legal protection from criminal acts of corruption in the Jiwasraya case study is intended to provide legal certainty and legal protection to help maintain the image of good government.